A Systematic Review of Beta Cell Function in Adults of Black African Ethnicity - M. Ladwa; O. Hakim; S. A. Amiel; L. M. Goff (Journal of Diabetes Research)
Background. Understanding ethnic differences in beta cell function has important implications for preventative and therapeutic strategies in populations at high risk of type 2 diabetes (T2D). The existing literature, largely drawn from work in children and adolescents, suggests that beta cell function in black African (BA) populations is upregulated when compared to white Europeans (WE). Methods. A systematic literature search was undertaken in June 2018 to identify comparative studies of beta cell function between adults (>age 18 years) of indigenous/diasporic BA and WE ethnicity. All categories of glucose tolerance and all methodologies of assessing beta cell function in vivo were included. Results. 41 studies were identified for inclusion into a qualitative synthesis. The majority were studies in African American populations (n=30) with normal glucose tolerance (NGT)/nondiabetes (n=25), using intravenous glucose stimulation techniques (n=27). There were fewer studies in populations defined as only impaired fasting glucose/impaired glucose tolerance (IFG/IGT) (n=3) or only T2D (n=3). Although BA broadly exhibited greater peripheral insulin responses than WE, the relatively small number of studies which measured C-peptide to differentiate between beta cell insulin secretion and hepatic insulin extraction (n=14) had highly variable findings. In exclusively IGT or T2D cohorts, beta cell insulin secretion was found to be lower in BA compared to WE. Conclusions. There is inconsistent evidence for upregulated beta cell function in BA adults, and they may in fact exhibit greater deficits in insulin secretory function as glucose intolerance develops.